The Effect of Work Motivation and Physical Work Environment on the Performance of PT SBCR Employees - Febriyanti, Riska; Sunimah (Journal Research of Social Science, Economics, and Management, 2026)
In the era of globalization and increasingly fierce business competition, high-quality human resources are crucial for achieving a company’s objectives. PT SBCR requires employees with optimal performance to face the existing business challenges. Therefore, this study focuses on analyzing the influence of work motivation and physical work environment on employee performance. This study aims to analyze the impact of work motivation and the physical work environment on employee performance at PT SBCR. An associative causal method is used as a quantitative approach. The research population consists of 137 permanent employees of PT SBCR, with data collected through questionnaires using a 5-point Likert scale. Data analysis was performed using SPSS version 26. The study found that work motivation has a positive and significant impact on employee performance, with a significance value of 0.048 and a regression coefficient of 0.255. Additionally, the physical work environment has the most dominant effect on employee performance, with an F value of 500.912, a significance of 0.000, and a regression coefficient of 0.639. Improving employee performance will be most effective when work motivation and the physical work environment are managed integratively and holistically, supporting the achievement of sustainable competitive advantage for the company.